DOI: 10.31274/etd-20210609-129
|View full text |Cite
|
Sign up to set email alerts
|

Pollinator response to prairie strips in the Iowa agricultural landscape

Abstract: I would like to thank my co-major professors, John Tyndall and Matthew O'Neal for advising me, but more importantly more for their encouragement and ridiculous jokes. I would also like to thank my committee member, Peter Wolter, for teaching me the ways of GIS, both throughout my bachelor's degree and master's degree. Thank you to all of the entomology folks who helped me in the field season and in the lab, who were always there for moral support including,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Treatments with prairie strips increased the average abundance of monarch butterflies by up to two‐fold compared to other row crop treatments. This aligns with another study that found a higher abundance of monarchs and other pollinators in farms with prairie strips than without strips (Murray, 2021). Beyond its biological significance, the increased abundance of monarchs has cultural and aesthetic values, which can support prairie strip adoption.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Treatments with prairie strips increased the average abundance of monarch butterflies by up to two‐fold compared to other row crop treatments. This aligns with another study that found a higher abundance of monarchs and other pollinators in farms with prairie strips than without strips (Murray, 2021). Beyond its biological significance, the increased abundance of monarchs has cultural and aesthetic values, which can support prairie strip adoption.…”
Section: Discussionsupporting
confidence: 92%
“…within prairie strips are not at harmful levels to monarch butterflies ( Danaus plexippus L.) (Hall et al, 2022). While prairie strips are known to increase the prevalence of bees and specific species of butterflies like monarchs (Kordbacheh et al, 2020; Murray, 2021; Schulte et al, 2017), the effects of prairie strips on butterfly diversity are not known and are what we address here.…”
Section: Introductionmentioning
confidence: 95%
“…and Oenothera spp. (Murray, 2021), which are typically planted during restoration projects. To capture a recent movement towards including conservation within agricultural landscapes, we also surveyed five fields with prairie strips (‘Prairie Strips’).…”
Section: Methodsmentioning
confidence: 99%
“…We estimated the landscape composition surrounding each potential apiary at both prairie strip and potential control sites within 1.6 km radius using ArcMap 10.5.1 (Redlands, U.S.) and selected control sites which had a landscape composition similar to the nearest prairie strip site (Table S3 and Figure S1 for detailed description of this method). In only one case was pollinator habitat (CP42) found (approximately 1 km from both a prairie strip site and a control site) that could have been another source of native flowering plants (Murray, 2021). Two of the control sites in 2017 were not reused in 2018 or 2019; all control sites in 2018 were reused in 2019.…”
Section: Methodsmentioning
confidence: 99%